Gen. Rosecrans [William Starke] (Tufts Archival Research Center, 2008)
2.5 x 4.25. "Rosecrans, William Starke 1819-1898; Brigadier general (Union Army) 1861-1865; Major General-brevet (inactive) rank 1865." These dates are approximate.